Comparison of the operative time for open door laminoplasty using titanium plate spacers or hydroxyapatite block spacers: a retrospective study - Takahiro Inui; Koichi Inokuchi; Yoshinobu Watanabe; Kentaro Matsui; Yuhei Nakayama; Keisuke Ishii; Takashi Suzuki; Taketo Kurozumi; Hirotaka Kawano (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Titanium plate (TP) and hydroxyapatite (HA) spacers are widely used during open-door laminoplasty, performed with the patient in a prone position. Reducing operative time is an important consideration, particularly to reduce the risk of postoperative complications in older patients. The purpose of this retrospective cohort study was to compare the operative time for open-door laminoplasty using TP or HA spacers. Methods Consecutive patients with a spinal cord injury, without bone injury, and ≥ 50 years of age were included. Multivariate regression analysis was used to compare the operative time between patients in the TP and HA group, adjusting for known factors that can influence surgical and postoperative outcomes. Propensity score matching was used to confirm the robustness of the primary outcome. The cumulative incidence of postoperative complications over 1-year after surgery was also compared. Results Of the 164 patients forming our study group, TP spacers were used in 62 and HA in 102. Operative time was significantly shorter for the TP (128 min) than HA (158 min) group (p < 0.001). Both multivariate and propensity score matching analyses confirmed a significant reduction in operative time for the TP, compared to HA, group (regression coefficient, − 30 min and − 38 min, p < 0.001 and p < 0.001, respectively). There was no significant difference in the cumulative incidence of postoperative complications. Conclusions The use of TP spacers reduced the operative time for cervical open-door laminoplasty by about 30 min, compared to the use of HA spacers, with no difference in the rate of postoperative complications.